A virtual acoustic black hole on a cantilever beam. (23rd June 2023) - Quaegebeur, Samuel; Raze, Ghislain; Cheng, Li; Kerschen, Gaëtan
Abstract: An acoustic black hole (ABH) consists of a tapered structure whose thickness follows a power-law profile. When attached to a host structure, an ABH localizes and traps the vibrational energy, which can then be dissipated through, e.g., a damping layer. However, effective vibration mitigation is known to occur only above a cut-on frequency which is inversely proportional to the length of the tapered structure. In this context, the main thrust of this paper is to replace a mechanical ABH by a digital controller so as to create a so-called virtual acoustic black hole (VABH), thus, freeing the ABH from possible mechanical constraints (e.g., compactness, manufacturing and fatigue issues). The proposed VABH is first detailed theoretically. The salient features and performance of the VABH are then demonstrated both numerically and experimentally using a cantilever beam as a host structure. Eventually, it is shown that the VABH significantly enlarges the applicability of the concept of an ABH. Highlights: A novel concept called virtual acoustic black hole is presented. Properties of the acoustic black hole effect are enhanced. The digital nature of the system enables to create designs unfeasible mechanically. Vibration mitigation performance is demonstrated experimentally. Excellent vibration reduction is achieved, also at low excitation frequencies.